Better crime prevention - Tilley, Nick (Criminology / sociology, 2024)
"Better Crime Prevention provides a critical guide to theory, research, ethics and politics in relation to crime prevention policy and practice, demonstrating what is involved in doing theoretically informed and realistic applied social science orientated to reducing harms"--